Penatalaksanaan impaksi gigi kaninus dengan cara kombinasi pembedahan dan ortodontik Management of impacted canine with combination of surgery and orthodontic - Franky Oscar (DiscoverSys Inc., 2011)
Complete tooth eruption, especially canine, will affect facial esthetic and the harmony. Surgical procedure will helpto expose an impacted tooth determining orthodontically into dental arch. Clinical and radiographic examinationshould be taken for locating the position of the tooth. The flap was designed differently between labially or palatallyimpacted canine. A 16 years old female came to clinic with Class III Angle dental and skeletal malocclusion with animpacted of upper left canine. She was treated with fixed orthodontic appliance using edgewise technique andsurgical exposure using closed-eruption technique. The proper diagnosis and management between oral andmaxillofacial surgery, and orthodontics will guarantee good result.